to solve for 'Y" I am thinking you should
5+2(x+y)=11
multiply through first
5+2x+2y=11
subtract 5
2x+2y=6
divide by 2
x+y=3
subtract x
y=3-x
-------------END---------
2007-01-10 18:23:28
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
Order of Operations is
Please Excuse My Dear Aunt Sally.
What does this stand for Parentheses Exponents Multiplcation Division Addition Subtraction.
The first step I'd take, though, is to subtract five from both sides of the equation. Actually add a negative 5 to both sides. This results in your equation becoming:
2(x+y)=6
Next I'd divide both sides by 2 to cancel out the 2 on the left side of the equation. This results in:
(x+y)=3
Now I can remove the parentheses:
x+y=3
Now I subtract x from both sides of the equation.
y=3-x
Now test this out by plugging values in for X to get Y for both equations. The first I'd try is x=3 This results in y=0 in the solved equation. Using the first results in:
5+2(x+y)=11
5+2(3+y)=11
5+6+2y=11
11+2y=11
2y=0
The only value of y that can make this true is if y=0
2007-01-10 18:25:47
·
answer #2
·
answered by hack_ace 4
·
0⤊
0⤋
here is what you do to find y in terms of x:
5 + 2(x + y) = 11
first combine like terms:
2(x + y) = 11-5
distribute your variables:
2x + 2y = 6
Put y by itself:
2y = 6 - 2x
Solve for y by dividing both sides by 2:
y = (6 - 2x) / 2
Simplify:
y = 3 - x
Do you have any more information on the product that you mentioned?
2007-01-10 18:18:25
·
answer #3
·
answered by pinkpearls 3
·
1⤊
0⤋
.........................5 + 2(x+y) = 11
then... 5 + 2x + 2y = 11
Rearranging for Y...... 2y = 11 - 5 - 2x
................................ .... = 6 - 2x
y = (6 - 2x)/2
.............................. y = 3 -x
To test this take a random number
e.g. Y = 10 ..... then X = -7 (10 = 3 - X)
Put it in the original equation
5 + 2(x+y) = 11
5 + 2(-7+10) = 11
5 + 2(3) =11
5 + 6 = 11
This will work for any number :)
2007-01-10 18:29:08
·
answer #4
·
answered by Yahya d 3
·
0⤊
0⤋
hi,
when you try to solve this, you will get a function like
y=3-x
that means you have a graph that has a slope of -1 and this crosses y axis at a point of 3 ( when x=0) and
x axis at a point of 3 ( when y=0). that line graph is the solution
if you can not draw a graph send me a pm, than i'll send it.
2007-01-10 18:25:52
·
answer #5
·
answered by ayhanakml 1
·
1⤊
0⤋
y=3-X
2007-01-10 18:23:12
·
answer #6
·
answered by uamir g 1
·
0⤊
0⤋
As people have shown
y= 3 - x
Finish by rewriting, so the answer is in the form:
y = -x + 3.
2007-01-11 02:08:49
·
answer #7
·
answered by S. B. 6
·
0⤊
0⤋
molve the y to the left of the = , the x + all numbers to the right
then you have written y as function of x
every x gives an y , wich is a solution
2007-01-10 19:03:15
·
answer #8
·
answered by gjmb1960 7
·
1⤊
0⤋
2y+2x=11-5=6
2y=6-2x
put x=0,
we get
2y=6
y=3
put x=1we get
2y=6-2=4
y=2
so on.
2007-01-10 18:30:48
·
answer #9
·
answered by Light 1
·
0⤊
1⤋
y= 3 - x
enjoy maths!!!
2007-01-10 18:26:42
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋